Dompet Dhuafa's Strategic Communication in Facing External Issues - Annisa Nursalsabillah; Atwar Bajari; Yanti Setianti (Persepsi: Communication Journal, 2023)
Every organization needs to design a strategic communication planning to carry out their program, including non-profit organizations. In the midst of limited operational funds, non-profit organizations need to think creatively in developing strategic communication designs, so they are capable to maintain their organizations, including in raising public funds. As represented by Dompet Dhuafa when facing the issue of misuse of funds by philanthropic individuals. When other philanthropists were affected by the case, Dompet Dhuafa managed to overcome it.The purpose of this study is to indicate and analyze the strategic communication implemented by Dompet Dhuafa when the organization is facing an issue.This study uses a case study qualitative research method through in-depth interviews and literature studies. The result obtained is that Dompet Dhuafa takes a strategic communication approach in the form of value strengthening so that stakeholders including donors interpret Dompet Dhuafa's philanthropic activities as a transparent and accountable institution. Through analysis surveys, message communication designs and media approaches as a form of communication strategy, Dompet Dhuafa was able to maintain their performance amidst the hectic issue of public trust in Indonesian philanthropy.